Ecoepidemiology and biology of eratyrus mucronatus stål, 1859 (Hemiptera: Reduviidae: Triatominae), a sylvatic vector of chagas disease in the brazilian amazon - Monte, Gersonval Leandro Silva; Tadei, Wanderli Pedro; Farias, Thaysa Marinho (Revista da Sociedade Brasileira de Medicina Tropical, 2014)
Introduction: Eratyrus mucronatus Stål, 1859 is a wild triatomine vector of Trypanosoma cruzi Chagas, 1909. Howev er, little is known regarding the biology and ecoepidemiology of this triatomine in the Brazilian Amazon. The present study describes the biology of E. mucronatus grown under laboratory conditions and the epidemiological aspects of its natural breeding sites. Methods: Five colonies were monitored in the fi eld for 3 years. Temperature and humidity measurements were taken in the mornings and afternoons at the natural breeding sites, and the behavior and distribution of the nymphs and adults were observed in the wild colony. We also monitored the life cycle under controlled laboratory conditions. Results: Some factors that were considered decisive for the establishment of these colonies were present at all of the colonies studied in the fi eld. These factors included an active termite nest, a vertebrate for repast, and dry and shaded substrates with temperatures of 24-28°C and with humidity of 80-90%. A generation was developed in 274 days under these microclimatic conditions in the laboratory. Conclusions: The climatic variables described in the fi eld indicate that these environmental parameters have a limiting effect on the dispersal and colonization of E. mucronatus to new environments. In addition, the long period of development to adulthood demonstrates that only one generation can develop per year even under the more favorable laboratory conditions. © 2014, Sociedade Brasileira de Medicina Tropical. All Rights Reserved.
Keywords: Active Termite Nest; Adult; Animals Dispersal; Anura; Arthropod; Bat; Biology; Breeding; Chagas Disease; Chagas Disease; Climate; Controlled Study; Digital Thermohygrometer; Environmental Parameters; Eratyrus Mucronatus; Eratyrus Mucronatus; Geographic Distribution; Global Positioning System; Hatching; Humidity; Incubation Time; Life Cycle; Lizard; Microbial Colonization; Molting; Nonhuman; Nymph; Temperature; Temperature Measurement; Triatominae; Triatominae; Animals; Chagas Disease; Classification; Defecation; Disease Carrier; Egg Laying; Feeding Behavior; Female; Life Cycle Stages; Male; Physiology; Transmission; Triatominae; Eratyrus Mucronatus; Hemiptera; Isoptera; Reduviidae; Triatominae; Trypanosoma Cruzi; Vertebrata; Animal; Chagas Disease; Defecation; Feeding Behavior; Female; Insect Vectors; Life Cycle Stages; Male; Oviposition; Triatominae